An emulsion applied to PP material and preparation method thereof
By using emulsions prepared by using polysilazane resin, low-chlorine content chlorinated polyolefins and carboxymethyl cellulose, the problem of poor adhesion and crack resistance of PP material surface coatings under low temperature conditions is solved, and high adhesion is achieved Focus, good hydrophobicity and excellent crack resistance.
Patent Information
- Application Number
- CN202310896897.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The prior art is difficult to improve the coating adhesion and crack resistance of the surface of PP materials under low temperature conditions, and conventional surface treatment methods are complex and the effects are uneven.
The emulsion is prepared by using raw materials such as polysilazane resin, chlorinated polyolefins with a chlorine content of less than 50 wt%, and carboxymethyl cellulose, and the adhesion and crack resistance of the emulsion are improved through specific preparation methods.
Under low temperature conditions, the emulsion coating has high adhesion and good hydrophobicity. There is no peeling and peeling during the low-temperature freeze-thaw cycle test, and it has high crack elongation and alkali treatment crack resistance.
Smart Images

Figure GDA0004949687840000041 
Figure GDA0004949687840000051 
Figure GDA0004949687840000061
Abstract
Description
Technical Field
[0001] The present application relates to the technical field related to coating preparation, and in particular to an emulsion applied to PP material and a preparation method thereof. Background Art
[0002] At present, polypropylene (PP), as one of the general plastics, is widely used in various fields such as chemical industry, medical treatment, machinery, transportation, etc. In order to improve the appearance quality of PP devices, extend the service life of PP devices, and improve their competitiveness in the sales market, it is very important to develop coatings for PP plastics.
[0003] However, the PP material has low surface energy, high crystallinity and very small polarity, making it difficult for the coating to have good adhesion on its surface; especially under low temperature conditions, many PP materials (such as the enclosures used in cold storage) have large grains, increased rigidity and poor toughness at low temperatures, which will further reduce the adhesion of the PP substrate surface. Therefore, conventional surface treatment methods such as flame treatment, plasma treatment and corona treatment are also difficult to increase the surface adhesion of the coating. In addition, these methods have complex procedures, uneven surface treatment effects, short activation time, and are prone to deformation of complex parts, increasing investment costs. On the other hand, even after the coating is applied to the surface of the PP substrate through surface treatment, the coating surface is prone to water condensation under low temperature and humid conditions, and the internal brittleness of the coating increases, resulting in poor crack resistance at low temperatures.
[0004] Therefore, there is an urgent need to propose an emulsion that has high adhesion, high crack resistance and can be stably applied to the surface of PP materials under low temperature conditions. Summary of the invention
[0005] In order to improve the adhesion and crack resistance of the PP material emulsion under low temperature conditions, the present application provides an emulsion applied to the PP material and a preparation method thereof.
[0006] The first purpose of the present application is to provide an emulsion applied to PP material, the second purpose of the present application is to provide a method for preparing the emulsion applied to PP material, and the third purpose of the present application is to provide an application of the emulsion applied to PP material.
[0007] The present application provides an emulsion applied to PP material using the following technical solution:
[0008] An emulsion applied to a PP material is prepared from the following raw materials in parts by weight:
[0009] 14-20 parts of polysilazane resin,
[0010] 3-7 parts of chlorinated polyolefin,
[0011] Additives 0.3-0.7 parts,
[0012] 6-9 parts of solvent;
[0013] The chlorine content of the chlorinated polyolefin is below 50%; the additive is selected from one or two of carboxymethyl cellulose and casein glue.
[0014] By adopting the above technical scheme, the emulsion prepared by using polysilazane resin, chlorinated polyolefin with a chlorine content of less than 50wt%, and carboxymethyl cellulose, when coated on PP material, has high coating adhesion and good hydrophobicity. The test pieces after low temperature and alkali treatment can achieve an elongation of more than 370, and no peeling occurs during the low temperature freeze-thaw cycle test. This may be because the polysilazane resin has low surface energy and better fatigue resistance as a resin matrix. Under the action of adding chlorinated polyolefin and carboxymethyl cellulose, the properties of the polysilazane resin can be changed, and the moisture and heat resistance and weather resistance can be improved.
[0015] Optionally, the additive consists of carboxymethyl cellulose and casein glue in a mass ratio of (0.25-0.4):1.
[0016] Preferably, the additive consists of carboxymethyl cellulose and casein glue in a mass ratio of 0.3:0.2.
[0017] By adopting the above technical scheme, compared with adding them separately, the water contact angle of the prepared emulsion is significantly increased, the hydrophobicity is improved, and the anti-crack elongation is significantly improved after the carboxymethyl cellulose and casein glue are mixed and added. It can be seen that the two have a synergistic effect in improving the anti-crack elongation and hydrophobicity. This may be because the carboxymethyl cellulose and casein glue can enhance the toughness and ductility of the emulsion coating when mixed and added, so that the internal components are evenly dispersed and the surface has a dense effect.
[0018] Optionally, the mass ratio of the lithium chloride to the solvent is 1:(6.7-14.4);
[0019] Preferably, the solvent is selected from dimethylacetamide and dimethylformamide;
[0020] Preferably, the solvent is dimethylacetamide.
[0021] By adopting the above technical solution, after adding lithium chloride, the coating peeling level is reduced, the emulsion adhesion is improved, the hydrophobicity is increased, and the low-temperature crack resistance elongation and alkali treatment crack resistance elongation are both improved. This may be because the addition of lithium chloride can promote the compatibility between chlorinated polyolefins and polysilazane resins and additives, and strengthen the emulsion dispersion. Optionally, the polysilazane resin has a number average molecular weight of 750-1000.
[0022] Preferably, the number average molecular weight of the polysilazane resin is 800-900.
[0023] Optionally, the chlorine content of the chlorinated polyolefin is 15-22 wt %.
[0024] By adopting the above technical scheme, the number average molecular weight of the polysilazane resin affects the crack resistance elongation and water contact angle of the emulsion. When the chlorine content of the chlorinated polyolefin is preferably 15-22wt%, the peeling grade reaches level 0, and it has high adhesion. The surface of the emulsion coating reaches a super-hydrophobic level, reducing the adhesion and condensation of water droplets in a low temperature and humid environment.
[0025] Optionally, the degree of substitution of the carboxymethyl cellulose is 0.4-1.5.
[0026] Preferably, the degree of substitution of the carboxymethyl cellulose is 0.7.
[0027] Optionally, the average particle size of the carboxymethyl cellulose is less than 100 μm.
[0028] Preferably, the average particle size of the carboxymethyl cellulose is 45-55 μm.
[0029] Preferably, the average particle size of the carboxymethyl cellulose is 50 μm.
[0030] By adopting the above technical scheme, the degree of substitution and particle size of cellulose have a certain influence on the performance of the emulsion, so that the low-temperature crack resistance elongation and alkali treatment crack resistance elongation of the emulsion coating can be partially improved, and the water contact angle is further increased; this may be because carboxymethyl cellulose with a degree of substitution of 0.7 has better rheological properties and stability; carboxymethyl cellulose with a particle size of less than 100 μm has good dispersibility, so that carboxymethyl cellulose does not easily clump.
[0031] The present application provides a method for preparing an emulsion applied to a PP material, comprising the following steps:
[0032] S1: Mixture preparation:
[0033] Putting polysilazane resin, additives, dimethylacetamide and other raw materials except chlorinated polyolefin into a reaction container and stirring to obtain the mixed solution;
[0034] S2: Raise the temperature to 80-120°C, add chlorinated polyolefin, and stir for 20-30 minutes;
[0035] S3: The temperature is lowered to 30-45° C., and the mixture is stirred and emulsified to obtain the emulsion applied to the PP material.
[0036] Preferably, the step S1 further comprises the following steps:
[0037] S11: carboxymethyl cellulose and lithium chloride are mixed, dissolved in dimethylacetamide, and casein glue is added under stirring to obtain a pre-solution;
[0038] S12: Put the polysilazane resin into a reaction container, add the pre-solution under stirring, and continue stirring for 20-30 minutes to obtain the mixed solution.
[0039] By adopting the above technical scheme, the emulsion applied to the PP material in the present application is simple to prepare and convenient for mass production, and by first mixing carboxymethyl cellulose and lithium chloride, then dissolving them in dimethylacetamide, and adding them to a reaction container under stirring and mixing with the polysilazane resin, the dispersion performance of each component can be improved, making the emulsion more stable.
[0040] The third purpose of the present application is to provide an application of an emulsion applied to PP materials; it is used to prepare coatings and paints, has good hydrophobicity, high adhesion, high crack resistance, and can be stably applied to the surface of PP materials.
[0041] In summary, the present application includes at least one of the following beneficial technical effects:
[0042] 1. The emulsion prepared by using polysilazane resin, chlorinated polyolefin with chlorine content less than 50wt%, and carboxymethyl cellulose has high coating adhesion and good hydrophobicity when applied to PP material. The test pieces after low temperature and alkali treatment can achieve an elongation of more than 370, and no peeling occurs during low temperature freeze-thaw cycle test;
[0043] 2. The degree of substitution and particle size of cellulose have a certain influence on the performance of the emulsion, so that the low-temperature crack elongation and alkali-treated crack elongation of the emulsion coating can be partially improved, and the water contact angle is further increased; this may be because carboxymethyl cellulose with a degree of substitution of 0.7 has better rheological properties and stability; carboxymethyl cellulose with an average particle size of less than 100μm has good dispersibility, so carboxymethyl cellulose is not easy to clump;
[0044] 3. The preparation method is simple and convenient for mass production. By first mixing carboxymethyl cellulose and lithium chloride, dissolving them in dimethylacetamide, and adding them into a reaction container under stirring to mix with the polysilazane resin, the dispersion performance of each component can be improved, making the emulsion more stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a schematic diagram of the production process of an embodiment of the present application.
[0046] Figure 2 It is a schematic diagram of the process of preparing the mixed solution in the embodiment of the present application. DETAILED DESCRIPTION
[0047] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present application.
[0048] Example
[0049] Examples 1-3
[0050] Examples 1-3 respectively provide an emulsion applied to a PP material.
[0051] The difference between the above embodiments is that the weight parts of the emulsion applied to the PP material are specifically shown in Table 1.
[0052] The number average molecular weight of the polysilazane resin is 750-1000; the chlorine content of the chlorinated polyolefin is below 48%, the substitution degree of the carboxymethyl cellulose is 0.4, and the average particle size is 100 μm.
[0053] Table 1: Composition of components in the emulsion applied to PP material provided in Examples 1-3
[0054]
[0055] The preparation method of the emulsion applied to the PP material in Examples 1-3 comprises the following steps:
[0056] S1: Mixture preparation:
[0057] Put the polysilazane resin into a reaction container, add carboxymethyl cellulose and dimethylacetamide into the reaction container under uniform stirring at 800-1200 r / min, and stir to obtain the mixed solution;
[0058] S2: heating to 80-120°C, adding chlorinated polyolefin to the mixed solution under nitrogen protection and stirring, and stirring for 20-30 minutes;
[0059] S3: The temperature is lowered to 30-45° C. and stirring is continued for 1.5-2 hours to emulsify and obtain the emulsion applied to the PP material.
[0060] Embodiment 4-7
[0061] Examples 4-7 provide an emulsion applied to a PP material.
[0062] The difference between Example 4-7 and Example 2 is that the additive component composition in the preparation of the emulsion applied to the PP material in Example 4-7 is different, as shown in Table 2.
[0063] Table 2: Composition of additives in the emulsion applied to PP material provided in Examples 4-7
[0064]
[0065] The preparation method of the emulsion applied to the PP material in Examples 4-7 comprises the following steps:
[0066] S1: Mixture preparation:
[0067] Put the polysilazane resin into a reaction container, add carboxymethyl cellulose, dimethylacetamide and casein glue into the reaction container under uniform stirring at 800-1200 r / min, and stir to obtain the mixed solution;
[0068] S2: heating to 80-120°C, adding chlorinated polyolefin to the mixed solution under nitrogen protection and stirring, and stirring for 20-30 minutes;
[0069] S3: The temperature is lowered to 30-45° C. and stirring is continued for 1.5-2 hours to emulsify and obtain the emulsion applied to the PP material.
[0070] Example 8
[0071] Example 8 provides an emulsion applied to a PP material.
[0072] The difference between Example 8 and Example 5 is that in the preparation of the emulsion applied to the PP material in Example 8, 0.7 parts by mass of lithium chloride is also added.
[0073] The preparation method of the emulsion applied to the PP material in Example 8 comprises the following steps:
[0074] S1: Mixture preparation:
[0075] Put the polysilazane resin into a reaction container, add carboxymethyl cellulose, dimethylacetamide, casein glue and lithium chloride into the reaction container under uniform stirring at 800-1200 r / min, and stir to obtain the mixed solution;
[0076] S2: heating to 80-120°C, adding chlorinated polyolefin to the mixed solution under nitrogen protection and stirring, and stirring for 20-30 minutes;
[0077] S3: The temperature is lowered to 30-45° C. and stirring is continued for 1.5-2 hours to emulsify and obtain the emulsion applied to the PP material.
[0078] Examples 9-12
[0079] Examples 9-12 provide an emulsion applied to a PP material.
[0080] The difference between Example 9-12 and Example 8 is that in the preparation of the emulsion applied to the PP material in Example 9-10, the added amounts of lithium chloride and dimethylacetamide are different.
[0081] The details are shown in Table 3.
[0082] Table 3: Composition of additives in the emulsion applied to PP material provided in Examples 9-12
[0083]
[0084] Example 13
[0085] Example 13 provides an emulsion applied to a PP material.
[0086] The difference between Example 13 and Example 8 is that the number average molecular weight of the polysilazane resin in Example 13 is 800-900.
[0087] Embodiment 14
[0088] Example 14 provides an emulsion applied to a PP material.
[0089] The difference between Example 14 and Example 13 is that the chlorine content of the chlorinated polyolefin in Example 14 is 15-22wt%.
[0090] Embodiment 15
[0091] Example 15 provides an emulsion applied to a PP material.
[0092] The difference between Example 15 and Example 14 is that the degree of substitution of carboxymethyl cellulose in Example 15 is 0.7.
[0093] Example 16
[0094] Example 16 provides an emulsion applied to a PP material.
[0095] The difference between Example 16 and Example 15 is that the average particle size of the carboxymethyl cellulose in Example 16 is 50 μm.
[0096] Embodiment 17
[0097] Example 17 provides an emulsion applied to a PP material.
[0098] The difference between Example 17 and Example 16 is: the different preparation methods.
[0099] The preparation method of the emulsion applied to the PP material in Example 17 comprises the following steps:
[0100] S1: Mixture preparation:
[0101] S11: carboxymethyl cellulose and lithium chloride are mixed and dissolved in dimethylacetamide, and casein glue is added under stirring to obtain a pre-solution; S12: polysilazane resin is placed in a reaction container, and the pre-solution is added to the reaction container under uniform stirring at 800-1200r / min, and stirring is continued for 20-30min;
[0102] S2: heating to 80-120°C, adding chlorinated polyolefin to the mixed solution under nitrogen protection and stirring, and stirring for 20-30 minutes;
[0103] S3: The temperature is lowered to 30-45°C and stirring is continued for 1.5-2h, and the emulsification is performed to obtain the emulsion applied to the PP material.
[0104] Comparative Example
[0105] Comparative Example 1
[0106] The difference between Comparative Example 1 and Example 2 is that when the emulsion applied to the PP material is prepared, the chlorine content of the chlorinated polyolefin is greater than 50wt%.
[0107] Comparative Example 2
[0108] The difference between Comparative Example 2 and Example 2 is that when preparing the emulsion applied to the PP material, the chlorinated polyolefin is replaced by chlorinated polypropylene.
[0109] Comparative Example 3
[0110] The difference between Comparative Example 3 and Example 2 is that when preparing the emulsion applied to the PP material, the polysilazane resin is replaced by bisphenol A type epoxy resin.
[0111] Comparative Example 4
[0112] The difference between Comparative Example 4 and Example 2 is that when preparing the emulsion applied to the PP material, the carboxymethyl cellulose is replaced by hydroxypropyl methyl cellulose.
[0113] Performance testing
[0114] 1. Low temperature crack elongation: After being stored at -20±5℃ for 1h and then restored to room temperature, the test is carried out in accordance with the provisions of 9.2.1 of GB / T16777-2008, with a tensile speed of 200mm / min.
[0115] 2. Alkali crack resistance elongation (tensile properties after alkali treatment): according to the provisions of 9.2.3 in GB / T16777-2008, the tensile speed is 200mm / min.
[0116] 3. Freeze-thaw resistance test: 4 PP specimens coated with emulsion are set as one group, and one specimen is kept as a control sample. After the other 3 specimens are placed at room temperature for 24 hours, the specimens are placed in tap water at (23±2)℃ for 18 hours, and then the specimens are placed in a low-temperature test box at (-20±2)℃ for 3 hours. The specimens are then taken out of the low-temperature test box and immediately placed in a constant temperature box at (50±2)℃ for 3 hours. This is one cycle, and the test is repeated in this way. During the test, the specimen should be observed once at the end of each cycle to determine whether the coating has cracking, delamination, shedding, swelling and discoloration, and record them. The cycle is repeated 5 times; at least 2 of the 3 specimens meet the technical requirements and are qualified.
[0117] 4. Hydrophobic performance test: After coating the emulsion on the PP material and curing it, a test sample is formed. The water contact angle is measured using pure water: the cleaned test sample is placed on a water platform, a certain volume of water droplets are accurately added, the image of the water droplets is captured with a camera, and then the contact angle of the water droplets on the image is measured using relevant software. The hydrophilicity and hydrophobicity are determined based on the measured water contact angle results. The larger the contact angle, the more hydrophobic the material surface is.
[0118] 5. Adhesion performance test (anti-peeling and scratch test).
[0119] The coating peeling resistance test is based on the "Scratch Test for Paint and Varnish Film" (GB / T9286-2021), and the main testing instrument is the cross-cut tester. After the emulsion is coated on the PP material and cured, a test sample is formed. Then the cross-cut tester is dragged horizontally, and the second drag is perpendicular to the previous one. Several small squares are drawn twice, and the tape is attached to the surface and then torn off. The peeling and shedding of the small squares of the coating are observed with a magnifying glass.
[0120] If no grid on the coating surface falls off, the coating peeling level is 0; if a small amount of coating is allowed to fall off and separate at the intersection of the coating cuts, but the affected area of the grid area is not more than 5%, the coating peeling level is 1; if the coating falls off at the intersection of the coating cuts or along the edges of the cuts, and the affected area is 5%-15%, the coating peeling level is 2; if a large area of coating is found to fall off along the cut edge, and the affected area is 15%-35%, the coating peeling level is 3; if large fragments of coating fall off along the cut edge, and the affected area is 35%-65%, the coating peeling level is 4; if severe peeling with an affected area greater than level 4 is found during the test, the coating peeling level is determined to be 5.
[0121] Test results
[0122] Table 4: The performance test results of the emulsions in Examples 1-18 and Comparative Examples 1-4 are as follows:
[0123]
[0124]
[0125] Results Analysis
[0126] The present application is described in detail below in conjunction with the experimental data provided in Tables 1-4.
[0127] In combination with Examples 1-3, Comparative Examples 1-4 and the test results, it can be seen that the emulsion prepared by using polysilazane resin, chlorinated polyolefin having a chlorine content of less than 50wt%, and carboxymethyl cellulose in Examples 1-3, when applied to PP material, the coating peeling grade can reach below level 2, the adhesion is high, and the water contact angle is above 110°. The test pieces after low temperature and alkali treatment can reach an elongation of more than 370, and no peeling occurs during 5 low temperature freeze-thaw cycle tests, having good adhesion and hydrophobicity, thereby improving the hydrophilicity of the polysilazane resin, the emulsion has good low temperature and alkaline elongation at break, and good hydrophobicity; therefore, at low temperatures, the coating is not easy to crack inside, the stability is high, and water droplets are not easy to condense on the surface of the coating, which overcomes the low temperature brittleness of the emulsion applied to the PP material at low temperatures and the paint and coating prepared by the emulsion to a certain extent, and has excellent application prospects.
[0128] Compared with Example 2, Comparative Example 1 uses a chlorinated polyolefin with a chlorine content higher than 50 wt%, and the water contact angle of the prepared emulsion is less than 90°, so that water droplets are not easy to slide off when adhering to the surface of the emulsion, which easily causes water droplets to condense on the surface of the coating, and water droplets are easily condensed when applied under low temperature and humid conditions.
[0129] Compared with Example 2, in Comparative Example 2, the chlorinated polyolefin was replaced with chlorinated polypropylene, and the adhesion performance of the emulsion was reduced to Level 5. The emulsion coating peeled off severely, and peeling occurred after two freeze-thaw cycles. The adhesion and low-temperature freeze-thaw resistance performance were poor.
[0130] Compared with Example 2, when the polysilazane resin in Comparative Example 3 is replaced with a bisphenol A epoxy resin, the adhesion performance of the emulsion is reduced to level 5, and peeling will occur after 5 freeze-thaw cycles. This may be because the polysilazane resin has low surface energy and better fatigue resistance as a resin matrix. Under the action of adding chlorinated polyolefins and carboxymethyl cellulose, the various properties of the polysilazane resin can be changed; and the ether bonds and hydroxyl groups in the bisphenol A epoxy resin are polar groups, which do not interact significantly with chlorinated polyolefins and carboxymethyl cellulose, have high wettability, poor moisture and heat resistance and weather resistance, so that the coating prepared under this component has poor adhesion.
[0131] Compared with Example 2, when the type of carboxymethyl cellulose in Comparative Example 4 was replaced with hydroxypropyl methylcellulose, the low-temperature crack elongation and alkali-treated crack elongation were reduced to 309% and 311%, respectively. It can be seen that the selection of different cellulose types has a significant effect on the crack elongation of the prepared emulsion, which may be due to the different dispersities of different celluloses in the solvent system.
[0132] It can be seen from this that in order to ensure that the emulsion coated on the PP material has excellent adhesion, good crack resistance and elongation, and resistance to low-temperature freeze-thaw, and the surface water contact angle is greater than 110°, it is necessary to use polysilazane resin, chlorinated polyolefin with a chlorine content of less than 50wt%, and carboxymethyl cellulose.
[0133] In combination with Example 2, Examples 4-7 and the test results, it can be seen that when carboxymethyl cellulose is replaced with casein glue, the performance of the prepared emulsion does not change significantly, but compared with the addition of carboxymethyl cellulose or casein glue alone, after the two are mixed and added, the water contact angle of the prepared emulsion is significantly increased, and the anti-crack elongation is significantly improved. It can be seen that the two have a synergistic effect in improving the anti-crack elongation and hydrophobic performance. This may be because when carboxymethyl cellulose and casein glue are mixed and added, the toughness and ductility of the emulsion coating can be enhanced, so that the components are evenly dispersed inside, the surface connection is highly stable, and a dense effect is achieved.
[0134] Combining Example 5, Example 8 and the test results, it can be seen that after adding lithium chloride, the coating peeling level is reduced, the emulsion adhesion is improved, the hydrophobicity is increased, and the low-temperature crack elongation and alkali treatment crack elongation are both improved. This may be because the addition of lithium chloride can promote the compatibility between chlorinated polyolefins and polysilazane resins and additives, and strengthen the dispersion of the emulsion, so that the dispersed systems support each other and achieve higher stability.
[0135] Compared with Example 8, Examples 9-12 further tested the effects of adding lithium chloride and dimethylacetamide in different weight parts and different proportions on the performance of the emulsion. After testing, the ratio of lithium chloride to dimethylacetamide was 1:(6.7-14.4) and had good performance. The best performance was achieved when the added weight parts of lithium chloride and dimethylacetamide were 9 parts and the ratio of the two was 1:10.
[0136] Combined with the test results of Examples 8 and 12-14, it can be seen that by further selecting a polysilazane resin with a number average molecular weight of 800-900, the crack resistance elongation of the emulsion is improved and the water contact angle is increased; the chlorine content of the chlorinated polyolefin is preferably 15-22wt%, the peeling grade reaches level 0, and the water contact angle is increased to 160°, reaching the super hydrophobic level, which can reduce the adhesion and condensation of water droplets in low temperature and humid environments.
[0137] Combined with the test results of Examples 14-16, it can be seen that the degree of substitution and particle size of cellulose have a certain influence on the performance of the emulsion. The emulsion prepared by carboxymethyl cellulose with a degree of substitution of 0.7 has a coating peeling grade of 0. The emulsion prepared by using carboxymethyl cellulose with an average particle size of 50 μm can partially improve the low-temperature crack elongation and alkali treatment crack elongation, and the water contact angle is further increased. This may be because carboxymethyl cellulose with a degree of substitution of 0.7 has better rheological properties and stability; carboxymethyl cellulose with an average particle size of 50 μm has good dispersibility, which improves the phenomenon that the carboxymethyl cellulose molecules that first contact water quickly absorb water and swell to form dry inside and wet outside particles, and are not easy to clump.
[0138] Combining Examples 16-17 and the test results, it can be seen that the order of adding lithium chloride significantly improves the hydrophobic performance. This may be because adding lithium chloride to dimethylacetamide first can enhance the dispersion promoting effect of lithium chloride on other components.
[0139] After testing, the emulsions prepared in Examples 1-17 of the present application have high adhesion, no paint peeling at low temperatures, high anti-cracking elongation, no peeling during freeze-thaw cycles, large water contact angles, and excellent hydrophobic properties. They can protect the surface of the PP substrate, which is brittle under low temperature conditions. Therefore, they are suitable for the application of PP materials in low temperature and humid environments, and are particularly suitable for the treatment of the surface of PP panels in cold storage.
[0140] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An emulsion applied to PP material, characterized in that: Made from the following raw materials in parts by weight: 14-20 parts of polysilazane resin, 3-7 parts of chlorinated polyolefin, Additives 0.3-0.7 parts, 6-9 parts of solvent; The chlorine content of the chlorinated polyolefin is below 50%, and the chlorinated polyolefin is a chlorinated polyolefin other than chlorinated polypropylene; the additive is selected from one or two of carboxymethyl cellulose and casein glue.
2. The emulsion applied to PP material according to claim 1, characterized in that The additive is composed of carboxymethyl cellulose and casein glue in a mass ratio of (0.25-0.4):
1.
3. The emulsion applied to PP material according to claim 1, characterized in that The raw materials for preparing the emulsion applied to the PP material also include 0.5-1.5 parts of lithium chloride.
4. The emulsion applied to PP material according to claim 3, characterized in that :The mass ratio of the lithium chloride to the solvent is 1:(6.7-14.4).
5. The emulsion applied to PP material according to claim 1, characterized in that : The number average molecular weight of the polysilazane resin is 750-1000.
6. The emulsion applied to PP material according to claim 1, characterized in that : The chlorine content of the chlorinated polyolefin is 15-22wt%.
7. The emulsion applied to PP material according to claim 1, characterized in that :The degree of substitution of the carboxymethyl cellulose is 0.4-1.
5.
8. The emulsion applied to PP material according to claim 1, characterized in that :The average particle size of the carboxymethyl cellulose is less than 100 μm.
9. A method for preparing an emulsion applied to PP material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Mixture preparation: Putting polysilazane resin, additives, dimethylacetamide and other raw materials except chlorinated polyolefin into a reaction container and stirring to obtain the mixed solution; S2: Raise the temperature to 80-120°C, add chlorinated polyolefin, and stir for 20-30 minutes; S3: The temperature is lowered to 30-45° C., and the mixture is stirred and emulsified to obtain the emulsion applied to the PP material.
10. The method for preparing an emulsion applied to PP material according to claim 9, characterized in that: The step S1 further comprises the following steps: S11: carboxymethyl cellulose and lithium chloride are mixed and dissolved in a solvent, and casein glue is added under stirring to obtain a pre-solution; S12: Put the polysilazane resin into a reaction container, add the pre-solution under stirring, and continue stirring for 20-30 minutes to obtain the mixed solution.
Citation Information
Patent Citations
Curable organopolysiloxane compositions and porous cured organopolysiloxane materials
CN102264800A
Multifunctional water-based environment-friendly heat transfer printing back glue composition and preparation method thereof
CN105038616A